Happiness Management: Theoretical, Practical and Impact - Firmansyah, Deri; Wahdiniwaty, Rahma (IJBLE Scientific Publications Community Inc., 2023)
The importance of happiness management is getting attention from the organization's HR because it relates to employee needs and motivations that are not only on financial operations but focus on overall employee welfare. This literature review aims to present the concept of happiness, happiness management practices in the workplace and the effects of happiness in life on activities and conditions relevant to the organization. Research findings, a positive and healthy organization can affect the happiness of its personnel. Companies must create a positive working atmosphere for employee satisfaction, Communication and collaboration, openness is needed which must support thinking, creativity and innovation, increase engagement and emotional work, and foster valuable social relationships. The meaning and purpose of life at work, considering it important to prioritize ethics, beliefs, and values, spiritually that true happiness is about being grateful for blessings and blessings, is also very likely to be associated with certain achievements and successes that are relative among human beings.